2009
DOI: 10.1007/s00520-009-0640-4
|View full text |Cite
|
Sign up to set email alerts
|

Marine phospholipids—a promising new dietary approach to tumor-associated weight loss

Abstract: These promising first results encourage further investigation of marine phospholipids in cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 49 publications
4
62
0
1
Order By: Relevance
“…The use of PLs (especially PC) reduced rheumatoid arthritis [134,135], pleurisy and leukocyte adhesion [134]. Treede et al [136] and Taylor et al [36] explained the anti-inflammatory effects of PC with inhibition of TNF alpha and TNF beta , whose reduced levels might also play positive roles on weight control. In addition, PC administration improves colitis mostly because it restores the appropriate gastrointestinal concentrations of this PL, which decrease with inflammation [137][138][139][140].…”
Section: Inflammation and Related Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of PLs (especially PC) reduced rheumatoid arthritis [134,135], pleurisy and leukocyte adhesion [134]. Treede et al [136] and Taylor et al [36] explained the anti-inflammatory effects of PC with inhibition of TNF alpha and TNF beta , whose reduced levels might also play positive roles on weight control. In addition, PC administration improves colitis mostly because it restores the appropriate gastrointestinal concentrations of this PL, which decrease with inflammation [137][138][139][140].…”
Section: Inflammation and Related Diseasesmentioning
confidence: 98%
“…Following hydrolysis, FAs from CM are incorporated into cell membranes in very selective manners [34,35], thereby altering their fluidity and function [36]. Sphingosine 1 phosphate allows SM to become part of a TAG and enter into the CM nucleus [37].…”
Section: Absorption Of Dietary Phospho-and Sphingolipidsmentioning
confidence: 99%
“…In addition to their anti-inflammatory effects, n-3 PUFA rich PC are also known to possess lipid lowering effects (Klimov et al, 1995, Bunea et al, 2004, Taylor et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Eight uncontrolled trials 6,8,10,13,[28][29][30][31] and three case series 7,32,33 focussed on the effect of fish oil and n-3-FA on cachexia in patients with advanced cancer (Supplementary Table 3).…”
Section: Uncontrolled Trialsmentioning
confidence: 99%
“…Another four cohort studies [28][29][30][31] and two prospective studies 8,10 reported results from a total of 159 patients. Patients were treated with EPA, DPA, marine phospholipids, fish oil or n-3-FA.…”
Section: Ries Et Al 299mentioning
confidence: 99%